2004
DOI: 10.1023/b:aseb.0000037428.41757.10
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Consent Behaviors in Same-Sex Relationships

Abstract: Consent is a key issue in defining sexual coercion yet few researchers have analyzed sexual consent attitudes and behaviors and, to date, there has been no published research examining sexual consent within same-sex relationships. The main objective of this study was to identify which behaviors people use to ask for and to indicate sexual consent to their same-sex partner(s). A Same-Sex Sexual Consent Scale was developed to measure both initiating and responding consent behaviors in same-sex relationships. Dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
87
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(106 citation statements)
references
References 21 publications
11
87
0
1
Order By: Relevance
“…This is consistent with previous research that has suggested that consent is often not explicitly granted, but that a range of behaviours can be seen as indicating consent, until such time as that consent is withdrawn (e.g. Beres, 2010;Beres, et al, 2004;Hall, 1998). The specific cues that participants draw on to determine whether or not consent is given will be discussed in the next theme of 'giving and refusing consent'.…”
Section: Consent As Processsupporting
confidence: 91%
See 1 more Smart Citation
“…This is consistent with previous research that has suggested that consent is often not explicitly granted, but that a range of behaviours can be seen as indicating consent, until such time as that consent is withdrawn (e.g. Beres, 2010;Beres, et al, 2004;Hall, 1998). The specific cues that participants draw on to determine whether or not consent is given will be discussed in the next theme of 'giving and refusing consent'.…”
Section: Consent As Processsupporting
confidence: 91%
“…It is well established that sexual consent or refusal may be undertaken verbally and non-verbally, and that very subtle indicators are used and understood by both men and women (Beres, 2010;Beres, Herold & Maitland, 2004;Kitzinger & Frith, 1999;O'Byrne, Hansen & Rapley, 2008;O'Byrne, et al, 2006), even in casual sexual relationships (Beres, 2010). In his sample of US college students, Hall (1998) found that consent was most frequently communicated non-verbally, and that consent is usually not specifically given for individual sexual acts that are part of an ongoing sequence.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the current research reinforces the need to better characterize forms of communication regarding sexual intentions and consent. There are clearly key disjunctures that are often overlooked by scholars in our field regarding many elements of communication interactions, including between actual desire, intentions, expression, and perception of willingness and consent, and the outcomes related to these components (Beres, Herold, & Maitland, 2004;O'Sullivan, 2005). Our findings emphasize the need to formulate, refine, and test new models of communication and negotiation in the sexual interactions of young dating samples that move us beyond traditional efforts that stress how individuals (and women, in particular) must use open and direct communication in their expressions of sexual desire.…”
Section: Discussionmentioning
confidence: 99%
“…Two people communicating with each other in this manner may, over time, gain clarity and confidence in their negotiation of consent as their skills generalize and strengthen [Fischer & Bidell, 2006]. Both heterosexual and homosexual college students typically rely solely on nonverbal signals to communicate sexual consent [Beres, Herold, & Maitland, 2004;Hickman & Muehlenhard, 1999]. No matter how consent is communicated, developing consent skills may be integrated with the development of related moral commitments such as respect for human dignity and care for human welfare.…”
Section: How Do Skills For Consent Develop?mentioning
confidence: 99%